A Pentacyclic Triterpenoid from Asteracantha longifolia Ness. - ALI, ABID; TRIPATHI, S.K. (Asian Journal of Chemistry, 2010)
A new pentacyclic triterpenoid 3β-acetoxyurs-18-ene (4) has been isolated from the aerial parts of Asteracantha longifolia Ness., alongwith lupeol (1), 16-hydroxy-26-methyltheptacosan-2-one (2) and stigmasterol (3). Their structures were elucidated by spectral analysis and chemical studies.